THE INNOVATION OF THE MINI TUBERCULOSISI SPUTUM EXAMINATION PROGRAM (MPIS-TB): A PILOT STUDY AT THE BANJARSENGON COMMUNITY HEALTH CENTER, JEMBER REGENCY - Grysha Viofananda Agung Kharisma Ade; Fahruddin Kurdi; Risha Putri Mahardika; Faizatul Ulya; Gevin Yensya; Nadya Rahmania Naristiti (Universitas Pelita Harapan, 2022)
In the era of the Covid-19 pandemic, the fear and anxiety of families of TB-positive patients increased, making it difficult for the sputum investigation program. Not coughing with phlegm, fear of being diagnosed with Covid-19, and feeling physically healthy are obstacles to the screening process. The aim of the study was to compare the sputum pots between the control and intervention groups in the innovation of the Mini TB Sputum Examination Program (MPIS-TB) in the Banjarsengon Community Health Center, Jember Regency. Quasy experimental with post test on 2 group design was using. This pilot study on 13 participants (6 different families) became group control ad intervention. Quickcheck Covid-19 East Java Provincial Health Office and SRQ-29 are used as a tool to approach the community to understand the differences in the diagnosis of TB and Covid-19. Effective cough therapy, chest physiotherapy, and simple inhalation for 3 consecutive days were also given to all participants to facilitate sputum production and release stimulation. The study results were 15,38% sputum pots were identified to return to the health center for laboratory analysis, 53,84% sputum pots returned intact (sealed sterile), and 30,76% sputum pots returned without sterile seals. The lack of return of sputum pots in 11 participants (84.6%) was due to several factors, namely not coughing with phlegm, fear of being diagnosed with Covid-19, and not feeling TB symptoms. The implementation of the MPIS-TB Program Innovation was successful with a sputum return ratio in the intervention and control groups of 40%: 0% so that in the future this program could be considered to be applied to the TB public health center program.